Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2): An Emerging Zoonotic Respiratory Pathogen in Humans - Ashwini Malla; Balamurugan Shanmugaraj; Sathishkumar Ramalingam (Journal of Pure and Applied Microbiology, 2020)
Two highly human pathogenic coronaviruses outbreak in the beginning of 21st century i.e. Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) and Middle East Respiratory Syndrome Coronavirus (MERS-CoV) in 2002 and 2012 respectively caused high pathogenicity and fatality rates in human populations. Recently, a new coronavirus named as SARS-CoV-2 or nCoV-2019 was first reported in Wuhan, China in December 2019 which is responsible for an acute human respiratory illness referred as Coronavirus Disease (COVID-19), an ongoing pandemic. SARS-CoV-2 is the third known highly pathogenic virus affecting human population. This virus spread globally within few weeks of first identification and nearly 5.52 million confirmed cases with more than 3,47,000 deaths reported as of May 25, 2020. Till date, there are no specific anti-viral drugs, therapies or vaccines to contain and prevent this infectious pathogen outbreak. The global spread of this virus to over 210 countries resulted in both human and economic losses, highlighting the need for an immediate imperative research exploration on prophylactic and therapeutic measures. Current knowledge and understanding of the pathogenesis of similar coronavirus SARS-CoV and MERS-CoV might be helpful for the rapid development of treatment strategies to prevent the further spread of this virus. In this review, we recapitulate the topical understanding on the structure, pathogenesis and epidemiology of SARS-CoV-2 that has emerged as a major health concern worldwide.